(untitled) (Swiss Medical Weekly, 2019)
OBJECTIVES Most urinary tract infections (UTIs) are treated empirically with antibiotics, making comprehensive resistance surveillance data essential to guide empiric regimens. We describe trends in the antibiotic resistance of urinary Enterobacteriaceae isolates in Switzerland between 2009 and 2016. METHODS We analysed data from routinely collected Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis urinary samples from community and hospital settings in Switzerland. The data were collected by ANRESIS, the national laboratory-based antimicrobial resistance surveillance system. Our analyses focused on resistance to antibiotics commonly prescribed for UTIs for the period 2009–2016. Only the first isolate per patient per year was included. RESULTS 297,200 urinary samples were included in the analysis, of which 246,656 (83.0%) were E. coli isolates. Overall, E. coli showed high susceptibility to 3rd/4th-generation cephalosporins, nitrofurantoin and fosfomycin, with the annual proportions of resistant isolates <6%, <5% and <2%, respectively, for all study years. Resistance to fluoroquinolones was >14% and increased over time (from 14.5% in 2009 to 19.3% in 2016). Resistance to cotrimoxazole was >20% for the whole study period. K. pneumoniae (n = 32,757; 11.0%) showed low resistance to cotrimoxazole and quinolones (<11% and <12%, respectively), while for P. mirabilis (n = 17,787; 6.0%) the proportion of resistant isolates was <35% for cotrimoxazole and <18% for quinolones. Even though quinolone resistance remained low for both pathogens (<12% for K. pneumoniae and <18% for P. mirabilis), it increased significantly over time. Proportions of isolates resistant to 3rd/4th generation cephalosporins remained low (<5% for K. pneumoniae and <2% for P. mirabilis), but in the case of K. pneumoniae they increased over time. CONCLUSIONS Swiss surveillance data confirm that resistance among uropathogenic E. coli isolates to nitrofurantoin and fosfomycin remains low. While resistance to 3rd/4th-generation cephalosporins also remains relatively low, it has been increasing and needs further surveillance. As for K. pneumoniae and P. mirabilis, high levels of susceptibility to 3rd-generation cephalosporins and quinolones were confirmed, while high prevalences of resistance to nitrofurantoin and fosfomycin discourage their use as first-line therapies for these pathogens.